Circular Economy Socialization for the General Public Around the Citarum River Basin - Ibrahim, Riza; Jaizul, Alim (International Journal of Research in Community Services, 2025)
Environmental issues are becoming increasingly concerning and endangering the life of the ecosystem on this earth. The environmental problems faced will certainly endanger human life now and for future generations. The issue of sustainability has become a very interesting study to discuss, both by academics, practitioners, relevant authorities, and even the general public, especially in developing countries. The concept of the five Rs: Reduce, Reuse, Recycle, Repair, and Recover, which has long been offered as a solution to reduce industrial waste, community waste, and family (household) waste, continues to be developed and is now the concept of the circular economy. The trending concept of the circular economy must be disseminated so that everyone realizes the importance of playing a role in realizing a circular economy for the sustainability of life in the future. This is the background to the implementation of the Student Creativity Program (PKM) with the topic of the Circular Economy for the General Public. The PKM was carried out offline and targeted the participants' understanding and interest in the circular economy. After the PKM implementation, understanding of the circular economy increased; where initially the community was not familiar with and familiar with the circular economy, after participating in the socialization showed a change in paradigm and attitudes, as well as knowledge about the circular economy.